2015
DOI: 10.5901/mjss.2015.v6n2s1p18
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on the Relationship between Democratic Classroom and Social Skills Development of Students

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…The Students perceived that it would be worthwhile giving them opportunity/freedom which includes expressing themselves in the class, developing their exceptional abilities, generating their own personalized ideas on the subject matter and having classroom discussions with fellow students. This finding is supported by Ahmad et al (2015) who reported that both female and male students in their study perceived democratic classroom environment as playing a great role in improving students' social skills development. Majority of the students agreed that they listen to one another carefully during a classroom discussion in a democratic classroom.…”
Section: Students' Perception About Classroom Democratizationsupporting
confidence: 58%
See 2 more Smart Citations
“…The Students perceived that it would be worthwhile giving them opportunity/freedom which includes expressing themselves in the class, developing their exceptional abilities, generating their own personalized ideas on the subject matter and having classroom discussions with fellow students. This finding is supported by Ahmad et al (2015) who reported that both female and male students in their study perceived democratic classroom environment as playing a great role in improving students' social skills development. Majority of the students agreed that they listen to one another carefully during a classroom discussion in a democratic classroom.…”
Section: Students' Perception About Classroom Democratizationsupporting
confidence: 58%
“…One of the active concepts and approaches in education which has been stressed over the years by research is democratic classroom environment (Ahmad et al, 2015). The concept of democratic classroom environment is attributed to the educational reformer "John Dewey" and his philosophical thoughts which staunchly support freedom and democracy in education (Louis, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, democracy which is a good regime also accepted as the ideal politic part of 21 st century (Kıncal, 2007). Implementation of the democracy is also possible with the fact has positive effects on the development of students' social skills (Ahmad, Said &Jusoh, 2015). The fact that classroom environment is important for gaining democratic values also proved in an experimental study done with the 6 th Grade middle school students in Istanbul in our country.…”
Section: Introductionmentioning
confidence: 80%
“…Teacher-student relationships also contribute to the formation of social skills (Berry & O'Connor, 2010;Vlachou et al, 2016). In addition to the relationship between teachers and students, the condition of the classroom environment can affect students' social skills, a democratic classroom has been shown to have a positive effect on the development of students' social skills (Ahmad et al, 2015). Furthermore, what needs to be considered in growing social skills is the pattern of parenting in the family (Hosokawa & Katsura, 2017;Şengönül, 2021;Takahashi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%